Antifungal activity of Aegle marmelos (L.) Corrêa and Cassia alata L. extracts against Candida krusei and Candida parapsilosis - Manivannan Veyakandah,; Nur Ain Izzati Mohd Zainudin,; Meenakshii Nallappan,; Sharina Omar,; Mohd Termizi Yusof,; Mohammad Noor Amal Azmai, (Penerbit Universiti Kebangsaan Malaysia, 2025)
Candidiasis is a fungal infection caused by several Candida species, including Candida krusei and Candida parapsilosis. It poses a significant threat to human health, particularly in immunocompromised individuals and those with underlying medical conditions. The rapid development of microbial resistance against antibiotics and the emergence of new strains are burdens to the global health community. Medicinal plants could be an excellent source for their potential antimicrobial effects. Therefore, this study aims to assess the antifungal action of Aegle marmelos and Cassia alata extracts on the growth and morphological changes of Candida krusei and Candida parapsilosis. The pathogens were cultured on media containing each extract individually. Itraconazole was used as a positive control, whereas dimethyl sulfoxide (DMSO) was used as a negative control. The minimum inhibitory concentration (MIC) and minimum fungicidal concentration (MFC) were determined by the microdilution method. All samples were processed for microscopy observations using a scanning electron microscope (SEM). The MIC of methanolic extract indicated that the leaf and unripe fruit of A. marmelos and C. alata against C. parapsilosis and C. krusei were similar at 75 mg/mL. Results of the MFC showed both pathogens were killed at a concentration of 150 mg/mL for both plant extracts. The MIC and MFC results of the methanolic extract indicated that the unripe fruit of A. marmelos exhibited fungistatic activity, while the leaves of both C. alata and A. marmelos demonstrated both fungicidal and fungistatic effects against C. parapsilosis and C. krusei. SEM observations showed significant changes in the morphology of C. krusei and C. parapsilosis compared to the control, in which the fungi were in normal form. The findings indicate the potential use of A. marmelos and C. alata methanolic extract as antifungal agents for candidiasis treatment. The extracts showed comparable inhibitory action to the commercial fungicide itraconazole.